Guided Imagery Technique in Reducing Anxiety in Pre-Operative Patients with Gangrene - Ervita, Ledy; Alhalawi, Zikri (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Anxiety is among the most prevalent mental health conditions, significantly affecting daily functioning and quality of life. This case report presents a comprehensive evaluation and intervention approach for a patient experiencing severe anxiety symptoms before undergoing surgery. A case study methodology was employed to document the clinical presentation, assessment, and treatment plan of a patient diagnosed with anxiety. Data collection included patient history, symptoms, and evaluation using standardized scales and non-pharmacological intervention such as guided imagery technique. The result such that the patient demonstrated a reduction in anxiety symptoms following the combined therapeutic approach. Psychological assessment scores improved and the patient reported enhanced coping mechanisms and overall well-being. The conclusion of this case report highlights the importance of an integrated therapeutic approach in managing anxiety. Non-pharmacological can significantly improve outcomes in anxiety in pre-operative patients.